2016
DOI: 10.1186/s13567-016-0313-5
|View full text |Cite
|
Sign up to set email alerts
|

Porcine aminopeptidase N binds to F4+ enterotoxigenic Escherichia coli fimbriae

Abstract: F4+ enterotoxigenic Escherichia coli (ETEC) strains cause diarrheal disease in neonatal and post-weaned piglets. Several different host receptors for F4 fimbriae have been described, with porcine aminopeptidase N (APN) reported most recently. The FaeG subunit is essential for the binding of the three F4 variants to host cells. Here we show in both yeast two-hybrid and pulldown assays that APN binds directly to FaeG, the major subunit of F4 fimbriae, from three serotypes of F4+ ETEC. Modulating APN gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Previous studies have found that F4 ETEC susceptibility is not associated with the genetic polymorphisms or expression differences in the APN gene, and that the α2–3,6,8 sialic acid of APN is sufficient for the binding of F4 fimbriae [ 16 , 33 ]. In our previous study, we found that changes in APN expression in IPEC-J2 cells could affect F4 ETEC adherence, and the results of yeast two-hybrid and pull-down assays confirmed that APN directly binds to the major fimbrial subunit FaeG in all three variants; however, we did not think that meta-periodate (NaIO 4 ) treatment had a significant impact on APN-FaeG binding in vitro [ 17 ]. We also found that the brush border membrane vesicles of F4 susceptible piglets have weaker F4 binding after 10 mM NaIO4 treatment for 30 min; this phenomenon is in accordance with earlier reports that the binding of F4ac to porcine enterocytes depends on glycosylation [ 16 , 34 ].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Previous studies have found that F4 ETEC susceptibility is not associated with the genetic polymorphisms or expression differences in the APN gene, and that the α2–3,6,8 sialic acid of APN is sufficient for the binding of F4 fimbriae [ 16 , 33 ]. In our previous study, we found that changes in APN expression in IPEC-J2 cells could affect F4 ETEC adherence, and the results of yeast two-hybrid and pull-down assays confirmed that APN directly binds to the major fimbrial subunit FaeG in all three variants; however, we did not think that meta-periodate (NaIO 4 ) treatment had a significant impact on APN-FaeG binding in vitro [ 17 ]. We also found that the brush border membrane vesicles of F4 susceptible piglets have weaker F4 binding after 10 mM NaIO4 treatment for 30 min; this phenomenon is in accordance with earlier reports that the binding of F4ac to porcine enterocytes depends on glycosylation [ 16 , 34 ].…”
Section: Discussionmentioning
confidence: 93%
“…Porcine neonatal jejunal IPEC-J2 cells and stable transfected cell lines pEC129-APN IPEC-J2 and pcDNA™6.2-GW/miR-APN IPEC-J2 (knocked down APN expression) were grown in RPMI 1640-F12 (1:1) (Gibco, Australia) supplemented with 10% fetal bovine serum (FBS, Gibco, Australia) at 37 °C in a humidified incubator with an atmosphere of 6% CO 2 [ 17 ]. We developed the monoclonal anti-F4 antibody and the polyclonal anti-APN antibodies in our laboratory [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the molecular mechanisms involved in TGEV infec- (Li et al, 2018;Melkebeek et al, 2012;Wang et al, 2018;Xia et al, 2016;Zhu et al, 2018). The production of pAPN site-specific edited pigs could be beneficial for understanding the pathogenesis of porcine deltacoronavirus and K88 for breeding porcine deltacoronavirus and K88-resistant pigs as well.…”
Section: Discussionmentioning
confidence: 99%